Torulaspora delbrueckii May Help Manage Total and Volatile Acidity of Santorini-Assyrtiko Wine in View of Global Warming - Georgios Sgouros; Athanasios Mallouchos; Dimitra Dourou; Georgios Banilas; Ioanna Chalvantzi; Yiannis Kourkoutas; Aspasia Nisiotou (Foods, 2023)
Non-Saccharomyces (NS) yeasts are gaining popularity in modern winemaking for improving wine quality. Climate change is one of the biggest challenges winegrowing now faces in warm regions. Here, Lachancea thermotolerans LtS1 and Torulaspora delbrueckii TdS6 combined with Saccharomyces cerevisiae ScS13 isolated from Assyrtiko grapes from Santorini island were evaluated in grape must fermentation with the aim to mitigate major consequences of temperature rise. Different inoculation protocols were evaluated, including simultaneous and sequential mixed-strain inoculations, displaying significant variation in the chemical and kinetic characteristics. Both LtS1 and TdS6 could raise the titratable acidity (TA). TdS6 also reduced the volatile acidity (VA) and was thus chosen for further evaluation in microvinifications and pilot-scale fermentations. Consistent with lab-scale trials, sequential inoculation exhibited the longest persistence of TdS6 resulting in minimum VA levels. Diethyl succinate, ethyl propanoate, and ethyl isobutyrate were significantly increased in sequential inoculations, although a decline in the net total ester content was observed. On the other hand, significantly higher levels of TA, succinic acid, and 2-methylpropanoic were associated with sequential inoculation. The overall performance of TdS6 coupled with a high compatibility with S. cerevisiae suggests its use in the fermentation of Santorini-Assyrtiko or other high sugar musts for the production of structured dry or sweet wines.